IMPLEMENTATION OF MOSQUE-BASED ISLAMIC EDUCATION MANAGEMENT; CASE STUDY AT BAITUL MUHLISIN MOSQUE PONOROGO - Bambang Wahrudin; Wawan Kusnawan; Rusmi (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study aims to analyze the implementation of mosque-based Islamic education management in the Baitul Muhlisin Mosque in Ponorogo, which is known as a transformative mosque model in the modern era. The phenomenon of low participation of the young generation in mosques and high education costs are the main background for the revitalization of the role of mosques. This study uses a qualitative approach with a descriptive case study. Data was collected through participatory observation, in-depth interviews with takmir administrators, and digital documentation from the mosque's official social media. Data analysis was carried out using the Miles, Huberman, and Saldaña interactive model which included data condensation, data presentation, and conclusion drawn. The results of the study show that the Baitul Muhlisin Mosque has succeeded in integrating four excellent programs, namely: 1) adaptive general and thematic routine studies, 2) professional management of Madrasah Diniyah, 3) educational scholarship program for five-time prayer pilgrims, and 4) providing pocket money for children participating in Fajr congregation. The findings of the study revealed that the use of material incentives functions as an effective positive reinforcement in conducting social engineering to form worship habits and the character of the younger generation. This success is supported by transparent and accountable management of Islamic philanthropy based on social media. This research has implications for the importance of repositioning mosques as financially independent civic centers to answer the challenges of moral degradation and access to education in Indonesia. Kata Kunci: Islamic Education Management, Mosque Management, Scholarships, Social Engineering, Baitul Muhlisin. Abstrak Penelitian ini bertujuan untuk menganalisis implementasi manajemen pendidikan Islam berbasis masjid di Masjid Baitul Muhlisin Ponorogo, yang dikenal sebagai model masjid transformatif di era modern. Fenomena rendahnya partisipasi generasi muda di masjid dan mahalnya biaya pendidikan menjadi latar belakang utama dilakukannya revitalisasi peran masjid. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus deskriptif. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam dengan pengurus takmir, serta dokumentasi digital dari media sosial resmi masjid. Analisis data dilakukan dengan model interaktif Miles, Huberman, dan Saldaña yang meliputi kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Masjid Baitul Muhlisin berhasil mengintegrasikan empat program unggulan, yaitu: 1) kajian rutin umum dan tematik yang adaptif, 2) manajemen Madrasah Diniyah yang profesional, 3) program beasiswa pendidikan bagi jamaah shalat lima waktu, dan 4) pemberian uang saku bagi anak-anak peserta Subuh berjamaah. Temuan penelitian mengungkapkan bahwa penggunaan insentif materiil berfungsi sebagai positive reinforcement yang efektif dalam melakukan rekayasa sosial (social engineering) untuk membentuk habituasi ibadah dan karakter generasi muda. Keberhasilan ini didukung oleh manajemen filantropi Islam yang transparan dan akuntabel berbasis media sosial. Penelitian ini berimplikasi pada pentingnya reposisi masjid sebagai pusat pemberdayaan umat (civic center) yang mandiri secara finansial guna menjawab tantangan degradasi moral dan akses pendidikan di Indonesia. Kata Kunci: Manajemen Pendidikan Islam, Manajemen Masjid, Beasiswa, Rekayasa Sosial, Baitul Muhlisin.